Social media for the 99%? Rethinking social movements' identity and strategy in the corporate web 2.0. Issue 2 (June 2016) - Ferrari, Elisabetta
In this article, I investigate the relationship between social movements and corporate social networking sites, by looking at content produced by Occupy Chicago on Twitter and Facebook during the protests of May 2012. Through an analysis of social media posts and activists' documents, I identify the functions that these platforms perform for the movement. My findings show a very limited importance of content that expresses the identity of the movement, spreads alternative news, and criticizes mainstream media, while the preponderance of protest reporting suggests that activists use social networking sites mainly to communicate "what they do, " rather than "who they are." I argue that the lack of identity-content is the result of the incompatibility between the decentralized political processes of Occupy and the individual-centric nature of social networking sites. I also suggest we need to rethink the relationship between social movements' identities and media strategies in light of a changed media environment.